Driving and Inhibiting Factors for Digital Transformation and Their Effects over the Advent of The Covid-19 Pandemic - Salume, Paula Karina; Cintra, Leandro Pinheiro; Silva, Leandro Libério da (Journal of Information Systems and Technology Management, 2022)
This paper aims to investigate driving and inhibiting factors for Digital Transformation (DT) and their effects on the advent over the COVID-19 pandemic from the perspective of business consultants.The research has been presented as descriptive in nature as well as on its general objective and on its approaching form, which come classified along as qualitative aspects. From the field of an investigation, four key dimensions emerged as the most relevant technology for DT: the value creation, the organizational structure and the culture adopted on businesses. Furthermore, it is worth highlighting the role of leadership as a key element in driving the team during a journey which requires a cultural transformation linked to DT.